Variability of Sea-Air Carbon Dioxide Flux in Autumn Across the Weddell Gyre and Offshore Dronning Maud Land in the Southern Ocean - Ogundare, Margaret Ojone; Fransson, Agneta; Chierici, Melissa; Joubert, Warren R.; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2021)
Sea surface fugacity of carbon dioxide (fCO2ssw) was measured across the Weddell gyre and the eastern sector in the Atlantic Southern Ocean in autumn. During the occupation between February and April 2019, the region of the study transect was a potential ocean CO2 sink. A net CO2 flux (FCO2) of -6.2 (±8; sink) mmol m-2 d-1 was estimated for the entire study region, with the largest average CO2 sink of -10.0 (±8) mmol m-2 d-1 in the partly ice-covered Astrid Ridge region near the coast at 68˚S and -6.1 (±8) mmol m-2d-1 was observed in the Maud Rise region. A CO2 sink was also observed south of 66˚S in the Weddell Sea. To assess the main drivers describing the variability of fCO2ssw, a correlation model using fCO2 and oxygen saturation was considered. Spatial distributions of the fCO2 saturation/O2 saturation correlations, described relative to the surface water properties of the controlling variables (chlorophyll a, apparent oxygen utilization, sea surface temperature, and sea surface salinity) further constrained the interplay of the processes driving the fCO2ssw distributions. Photosynthetic CO2 drawdown significantly offsets the influence of the upwelling of CO2-rich waters in the central Weddell gyre and enhanced the CO2 sink in the region. FCO2 of -6.9 mmol m-2 d-1 estimated for the Weddell gyre in this study was different from FCO2 of -2.5 mmol m-2 d-1 in autumn estimated in a previous study. Due to low CO2 data coverage during autumn, limited sea-air CO2 flux estimates from direct sea-surface CO2 observations particularly for the Weddell gyre region are available with which to compare the values estimated in this study. This highlights the importance of increasing seasonal CO2 observations especially during autumn/winter to improving the seasonal coverage of flux estimates in the seasonal sea ice-covered regions of the Southern Ocean.